(untitled) - Hoffer, Jeffrey A. (Upper Saddle River, 2005)
Complex, challenging, and stimulating, this book addresses information system analysis and design; it is full of information that shows the organizational process that a team of business and systems professionals use to develop and maintain computer-based information systems. It stresses the importance of responding to and anticipating problems through innovative uses of information technology. The book provides an excellent foundation for systems development, then goes on to making the business case, analysis, design, implementation and maintenance. For future systems analysts, or for those information technology that need a great resource for implementing new ideas and strategies for success.
Keywords: System design,System analysis